Water quality of outdoor household water tank / Laily Suraya Zakarya - Zakarya, Laily Suraya (2017)
Watertank is widelyused in allcountries as water storagetools to keep clean water. Exposed watertank maygive harmful effects dueto weathering. Traceelements such as chlorine, phosphate, nitrate that came from the tank maydiffuseinto thewaterandinfestation of microorganism carried by insects that inhabit the water tank could causeahugeproblem to the consumers. Theaimof this studywas to detect dissolve tracemetal from outdoor household watertank and to screenforpotential harmful bacteria from water samplein outdoor household water tank. Thequantityof tracenitrate andphosphate was measured byusingUV-Vis spectroscopywhile chlorinewasmeasured by using titration method. In this study, the resultshowed the water sample contained high concentration of chlorinecompareto standard drinkingwaterbyMinistryofHealth, meanwhile, concentration of nitrate andphosphate werein asafeamountindicated byMinistryof Health. Theprobabilityof bacteriain thewater samplewas categorized as Shigella spp..